Prevalence and spectrum of bacterial co‐infection during fungal keratitis - Pate, J C (BMJ Group, 2006)
AIMS: To estimate the propensity of keratomycosis for parallel or secondary bacterial infection and to explore affinities among fungal and bacterial co‐isolates. METHODS: A retrospective review of laboratory records over 24 years yielded 152 episodes of culture positive fungal keratitis. After collating 65 corneal specimens having bacterial co‐isolates, polymicrobial co‐infection was defined as detection of concordant bacteria on smear and culture or on two or more different media. RESULTS: 30 (20%) keratomycoses met laboratory criteria for polymicrobial infection. The risk of bacterial co‐infection was 3.2 (95% confidence interval, 1.7 to 5.8) times greater with yeast keratitis than with filamentous fungal keratitis. CONCLUSIONS: Bacterial co‐infection occasionally complicates fungal keratitis, particularly candidiasis.